2022
DOI: 10.1109/tuffc.2021.3128227
|View full text |Cite
|
Sign up to set email alerts
|

Multiperspective Bistatic Ultrasound Imaging and Elastography of the Ex Vivo Abdominal Aorta

Abstract: Knowledge of aneurysm geometry and local mechanical wall parameters using ultrasound (US) can contribute to a better prediction of rupture risk in abdominal aortic aneurysms (AAAs). However, aortic strain imaging using conventional US is limited by the lateral lumen-wall contrast and resolution. In this study, ultrafast multiperspective bistatic (MP BS) imaging is used to improve aortic US, in which two curved array transducers receive simultaneously on each transmit event. The advantage of such bistatic US im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…In addition, large aperture studies with an external tracker showed a gain for deep imaging [44] and it is expected that CoMTUS should only improve on this. Previous studies with two curved array transducers show that multiperspective images calibrated using image registration still can improve the reconstruction of particularly challenging applications such as the aortic wall and provide significant benefits for strain imaging [9]. Bottenus et al [10] quantified the accuracy required to coherently merge information from different probe locations in 2-D imaging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, large aperture studies with an external tracker showed a gain for deep imaging [44] and it is expected that CoMTUS should only improve on this. Previous studies with two curved array transducers show that multiperspective images calibrated using image registration still can improve the reconstruction of particularly challenging applications such as the aortic wall and provide significant benefits for strain imaging [9]. Bottenus et al [10] quantified the accuracy required to coherently merge information from different probe locations in 2-D imaging.…”
Section: Discussionmentioning
confidence: 99%
“…These image fusion techniques based on the exploitation of multiple points of view can reduce view-dependent artefacts [7] and improve contrast [5]. Recent studies have demonstrated that the contrast improvements also enhance motion and strain estimations from US image data [8] [9]. However, such approaches do not improve the diffraction-limited resolution and they cannot directly achieve the gains in sensitivity that could be realized if the multiple arrays were coherently combined into a one large effective aperture [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This results in four different combinations of transmit (T) and receive (R). [29] constructed. The term bistatic imaging originates from radar technology [25], where the position between transmitter and receiver is separated, opposed to monostatic imaging where the transmitter and receiver are co-located.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, no separate recording and temporal registration are needed. Improvements of this method in image quality and vascular strain imaging have been demonstrated in a mock circulation setup using a porcine aorta [25][26][27]. However, for cardiac imaging, considering the limited imaging windows, asymmetrical and inhomogeneous deformation pattern, and high strain levels in different regions of LV, a different imaging setup and strain compounding method are required.…”
Section: Introductionmentioning
confidence: 99%